1995
DOI: 10.1002/tcm.1770150609
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic transformation by quartz in the BALB/3T3/A31‐1‐1 cell line and the effects of associated minerals

Abstract: Quartz, the most common form of crystalline silica, was tested quantitatively for neoplastic transformation in the mouse embryo cell line, BALB/3T3/A31-1-1. Five quartz dust samples of respirable size [Min-U-Sil 5 (MQZ); hydrofluoric-acid-etched MQZ (HFMQZ); Chinese standard quartz (CSQZ); DQ12; and F600] all induced significant levels of neoplastic transformation, showing dose-dependent increases in the frequency of morphologically transformed foci at lower tested doses and a plateau level of response at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Both treatments do indeed modify the silanol distribution. Similarly, a rough correspondence can be noted between the evaluated toxicity and the expected abundance of reactive silanols in those studies where a different biological activity among silica specimens was reported. , , Here, we would like to discuss the most obvious questions that our proposal may elicit.…”
Section: Is the Model Proposed Consistent With Past Research?mentioning
confidence: 79%
See 1 more Smart Citation
“…Both treatments do indeed modify the silanol distribution. Similarly, a rough correspondence can be noted between the evaluated toxicity and the expected abundance of reactive silanols in those studies where a different biological activity among silica specimens was reported. , , Here, we would like to discuss the most obvious questions that our proposal may elicit.…”
Section: Is the Model Proposed Consistent With Past Research?mentioning
confidence: 79%
“…Many studies showed that crystalline silica particles are cytotoxic, inflammogenic, trigger the production of inflammatory substances, oxidants and growth factors from cells, can damage membranes, etc. , However, when the same test was performed on a variety of silica samples either collected or prepared ad hoc, the extent and even the nature of the cellular response varied. , If the quartz particles were associated with other minerals or elements (such as aluminum, iron, and carbon), effects were in some cases enhanced or blunted in others. , Also, deposition of polymers or other substances on the particle surface modified (mostly inhibited) cellular responses. …”
Section: Variability Of Quartz Hazardmentioning
confidence: 99%
“…The ability of quartz to induce dose-dependent morphological transformation of cells in vitro has been demonstrated in experiments with Syrian hamster embryo cells and mouse embryo BALB/c-3T3 cells [Saffiotti and Ahmed 1995]. Gu and Ong [1996] also reported a significant increase in the frequency of transformed foci of mouse embryo BALB/c-3T3 cells after treatment with Min-U-Sil-5 quartz.…”
Section: Genotoxicity and Related Effectsmentioning
confidence: 98%
“…After inoculation into naked mice of cells which had been transformed by Min-U-Sil 5, by hydrofluoric acid-etched Min-U-Sil 5 or by Sikron F 600, in each case 5/5 animals developed fibrosarcomas. In some of the transformed cell lines, the expression of oncogenes was shown to be increased (Saffiotti and Ahmed 1995); this could be evidence of the induction of gene amplification. Concentration-dependent increases in cell transformation rates were seen in SHE cells treated with Min-U-Sil and α-quartz from concentrations of 2 and 10 µg/cm 2 , respectively (Hesterberg and Barrett 1984).…”
Section: Cell Transformation Studiesmentioning
confidence: 99%